The translational inhibitor 4E-BP is an effector of PI(3)K/Akt signalling and cell growth in Drosophila. - Miron, M.; Verdu, J.; Lachance, P.E.D.; Birnbaum, M.J.; Lasko, P.F.; Sonenberg, N. (Nature Cell Biology, 2001)
The initiation factor 4E for eukaryotic translation (eIF4E) binds the messenger RNA 5'-cap structure and is important in the regulation of protein synthesis. Mammalian eIF4E activity is inhibited when the initiation factor binds to the translational repressors, the 4E-binding proteins (4E-BPS). Here we show that the Drosophila melanogaster 4E-BP (d4E-BP) is a downstream target of the phosphatidylinositol-3-OH kinase (PI(3)K) signal-transduction cascade, which affects the interaction of d4E-BP with eIF4E. Ectopic expression of a highly active d4E-BP mutant in wing-imaginal discs causes a reduction of wing size, brought about by a decrease in cell size and number. A marked reduction in cell size was also observed in post-mitotic cells. Expression of d4E-BP in the eye and wing together with PI(3)K or dAkt1, the serine/threonine kinase downstream of PI(3)K, resulted in suppression of the growth phenotype elicited by these kinases. Our results support a role for d4E-BP as an effector of cell growth.